The Usefulness of Ozone-Stabilized Municipal Sewage Sludge for Fertilization of Maize (Zea mays L.) - Małgorzata Szostek; Patryk Kosowski; Ewa Szpunar-Krok; Marta Jańczak-Pieniążek; Natalia Matłok; Karol Skrobacz; Rafał Pieniążek; Maciej Balawejder (Agriculture, 2022)
Sewage sludge generated in the wastewater treatment process is a waste material and a serious environmental nuisance. Due to its specific properties, the management and final disposal of sewage sludge is a considerable problem also in Poland. Ozonation of sewage sludge is the most commonly used process based on the use of oxidizing agents for stabilization of the waste. This process results in substantial reduction of the sludge volume and simultaneous production of small amounts of toxic by-products. Despite the effectiveness of ozone in sanitation and reduction of sludge amounts and in improvement of many parameters, still little is known about the use of ozonated sewage sludge for agricultural purposes, e.g., fertilization of arable crops. Therefore, the present study was an attempt to evaluate the effect of ozone-stabilized sewage sludge on maize development in initial stages of growth in pot experiment conditions. We analyzed the effect of ozone-stabilized sewage sludge in soil on dry matter yields of aboveground parts of maize. We also conducted physiological measurements of chlorophyll content, fluorescence, and exchange. Additionally, the content of macro- and microelements and toxic heavy metals in aboveground maize biomass was determined. The ozone-stabilized sewage sludge exerted a positive impact on all maize parameters in the initial stage of growth. Compared to the control, plants fertilized with this type of sludge were characterized by a 50% higher yield of aboveground biomass and over 80% higher content of chlorophyll. Furthermore, the content of most macro- and microelements in the aboveground biomass was generally higher in plants fertilized with the ozonated sludge than in plants from the other experimental variants. The chlorophyll fluorescence and gas exchange parameters in plants fertilized with ozonated sludge were improved. No excessive accumulation of Pb and Cd was detected. The present results have confirmed that ozone-stabilized sewage sludge can be used for cultivation of agricultural plants, as it improves utilization of deposited nutrients. The improved bioavailability of nutrients was associated with ozonation-induced initial degradation of organic matter and release of deposited plant nutrients.